A Reproducible Capillary Gas Chromatographic Technique for the Determination of Specific Terpenes in Grape Juice and Wine - Marais, J. (South African Journal of Enology and Viticulture, 2017)
A reliable and highly reproducible technique for the Freon 11 extraction of 16 terpenes from grape juice and wine and their gas chromatographic analyses is presented. Terpene concentrations were calculated as relative values by means of an internal standard. Standard deviations of the terpenes analysed varied between 1,2% and 13,9% for non-settled grape juice and between 2,0% and 5,2% for wine. Variation in gas chromatographic retention times was between 0,04 and 0,1 minutes. The freon extracts of grape juice and wine could be stored at minus 12°C for up to six days without marked changes occurring in the relevant terpene concentrations.